2020
DOI: 10.1016/j.nut.2020.110995
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects associated with immune modulation by selected lactic acid bacteria in a Parkinson's disease model

Abstract: Neuroprotective effects associated to immune modulation by selected lactic acid bacteria in a Parkinson's disease model, Nutrition (2020), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 38 publications
5
62
0
Order By: Relevance
“…Previous research has also proven the neuroprotective effects of Lactobacillus administration in MPTP- and rotenone-induced PD models as well as PD patients ( Liao et al., 2020 ; Ilie et al., 2021 ; Lu et al., 2021 ). In agreement with our results, Lactobacillus was previously reported to attenuate MPTP-induced neuroinflammation by preventing glial hyperactivation, and inhibiting the levels of TNF-α , and IL-6 ( Liao et al., 2020 ; Perez Visñuk et al., 2020 ). Intriguingly, Lactobacillus -based probiotics increased the levels of both dopamine and serotonin in the striatum, thus ameliorating the anxiety-like behavior of germ-free mice ( Liu WH et al., 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Previous research has also proven the neuroprotective effects of Lactobacillus administration in MPTP- and rotenone-induced PD models as well as PD patients ( Liao et al., 2020 ; Ilie et al., 2021 ; Lu et al., 2021 ). In agreement with our results, Lactobacillus was previously reported to attenuate MPTP-induced neuroinflammation by preventing glial hyperactivation, and inhibiting the levels of TNF-α , and IL-6 ( Liao et al., 2020 ; Perez Visñuk et al., 2020 ). Intriguingly, Lactobacillus -based probiotics increased the levels of both dopamine and serotonin in the striatum, thus ameliorating the anxiety-like behavior of germ-free mice ( Liu WH et al., 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Of interest, hyperhomocysteinemia is associated with neuroinflammation in a murine model of vascular dementia (87). The use of folate-producing probiotic strains can be useful in reduction of neuroinflammation, as indicated by decreased levels of pro-inflammatory cytokines, and by improvement of motor behavior in PD (88). Some RCTs suggest that treatment with folate and vitamin B12 could be helpful in the long-term management of specific populations affected by depressive symptoms.…”
Section: Focus On Folic Acid and Neuroinflammationmentioning
confidence: 99%
“…Caroline Xie et al showed that probiotics ameliorated hippocampal-dependent cognitive deficits in preclinical PD models (Xie and Prasad, 2020). Perez Visnuk et al showed that decreased levels of inflammatory cytokines IL-6 and TNF-α in serum and increased levels of antiinflammatory cytokines IL-10 in serum and brain tissue in the probiotic-treated PD mice (Perez Visñuk et al, 2020). A study by Athari Nik Azm et al showed that probiotics reduced oxidative stress biomarkers and amyloid plaque formation in mice (Athari Nik Azm et al, 2018).…”
Section: Discussionmentioning
confidence: 99%